The Sustainability of The Netflix's Business Processes With Knowledge Risk Management Approach - Gustian Rama Putra; Wahyu Sardjono; Taruma Leo Wijaya; Erna Selviyanti; Asep Saepulrohman (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2023)
The Squid Game film is a film that is very familiar among the public because the story, storyline, and also the quality provided gives a very good impression that can be accessed by the public through an application called Netflix. Not surprisingly, many people remember their childhood in these stories. However, on the side of its very global fame, there are several issues that must be faced by Netflix in showing the Squid Game film that can threaten the sustainability of Netflix's business process itself. Through this research, we will analyze the factors that cause Netflix to face the worst scenario in showing the Squid Game film through Factor and Regression analysis on a predetermined model. The results stated that there were 9 factors that caused Netflix to have to deal with this problem.